Intervensi Kesehatan Mental terhadap Respon Biologis Oral - Khodijah, Khodijah; Chasanah, Niswatun; Nabilah, Nasywa (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2025)
Mental health is an integral component in maintaining physiological homeostasis, including the structure and function of oral tissues. Disorders such as stress and depression can trigger biological alterations through activation of the autonomic nervous system, increased cortisol secretion, and reduced mucosal immunity. Objective : This study aims to analyze the relationship between mental health disorders and oral biological responses based on the latest scientific evidence. Methods : A literature review of scientific articles published between 2020 and 2025, obtained from the PubMed, ScienceDirect, and Google Scholar databases, focusing on oral manifestations such as bruxism, xerostomia, and periodontitis. Result : revealed that psychological distress correlates with increased periodontal inflammation, salivary dysfunction, and immune dysregulation within the oral cavity. These findings confirm the physiological connection between mental health and oral biological function, which requires understanding within an interdisciplinary framework. Keywords: mental health, stress, oral biology, inflammation